Investigation of Reinforced Concrete Column Containing Metakaolin and Fly Ash Cementitious Materials - R. Dharmaraj; Sudhir Singh Bhadauria; K. Mayilsamy; J. Thivya; Alagar Karthick; I. Baranilingesan; V. Mohanavel; M. Muhibbullah; Sameh M. Osman (Advances in Civil Engineering)
Nowadays, high-performance concrete is employed in the building sector all over the world. For a strong and durable construction, high performance appears to be a better option. These specially designed types of concrete are made using both conventional and unique materials to fulfill a combination of performance requirements. The objective of this experiment is to investigate the behaviour of short and long columns made of high-performance concrete (HPC). In this study, HPC was manufactured by essential denominators such as cement, fine aggregate, coarse aggregate, water, and mineral admixtures such as metakaolin and fly ash at different replacement levels. The high-performance concrete (HPC) was designed with compressive strength (CS) of about 60 N/mm2. The mixture was developed under the guidelines in modified ACI 211.4R-93. All combinations have the same 0.30 water binder ratio (W/B) and are utilized to achieve improved workability with the addition of a superplasticizer for a chemical admixture, namely, CERAPLAST 300. Seven proportions are cast with 0%, 5%, 7.5%, and 10% replacement of cement with metakaolin and another set of specimens with 5%, 7.5%, and 10% replacement with metakaolin along with a constant 10% replacement of fly ash. For the investigation of strength properties, specimens (cube, prism, and cylinders) such as compressive strength (CS) (3, 7, 28, 56, and 90 days), flexural (FS) and tensile strength (STS) (28 days) and modulus of elasticity were cast (28 days). Totally 14 columns, 7 for short and long columns, were cast, each cured for 28 days. These specimens have been tested in the 1000 kN loading frame. All small columns were tested with concentrated compression, whereas long columns were investigated with little concentration and uniaxial bending. The compressive strength of HPC with 7.5 percent metakaolin and 10 percentage fly ash (MR6) is 59 MPa, 7.34% greater than the compressive strength of reference concrete.